ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA INDIVIDU PENGGUNA SISTEM INFORMASI DENGAN MENGGUNAKAN MODEL DELONE DAN MCLEAN (Studi Kasus pada Pemakai Aplikasi Accounting Information System PT Pegadaian (persero) Cabang Pembantu Singosari) - Imfita Nur Rosidah; Anik Malikah; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThe study aimed to analyze of the Factors Affecting the Individual Performance ofInformation System Users Using the DeLone and McLean Model (Case Study onAccounting Information System Users at PT Pegadaian (persero) SingosariAuxiliary Branch). The method used is Partial Least Square (PLS). The results ofthe study found that the quality of information systems does not affect but thequality of information, service quality, and conditions that facilitate proven jointlyaffect the performance of individual users of information systems throughinformation system user satisfaction. The quality of information systems has nosignificant positive effect on the satisfaction of information system users.Information quality, service quality, and facilitating conditions have a significantpositive effect on information system user satisfaction. Information system usersatisfaction has a significant positive effect on the performance of individualinformation system users.Keywords: Model D & M, Information System and Individual Performance.